Measuring motor imagery using psychometric, behavioral, and psychophysiological tools - Collet, C.; Guillot, A.; Lebon, F.; MacIntyre, T.; Moran, A. (Exercise and Sport Sciences Reviews, 2011)
This review examines the measurement of motor imagery (MI) processes. First, self-report measures of MI are evaluated. Next, mental chronometry measures are considered. Then, we explain how physiological indices of the autonomic nervous system can measure MI. Finally, we show how these indices may be combined to produce a measure of MI quality called the Motor Imagery Index.